Sclerostin Antibody Mitigates Estrogen Deficiency-Inducted Marrow Lipid Accumulation Assessed by Proton MR Spectroscopy - Shaojun Li; Bingcang Huang; Bo Jiang; Mingjun Gu; Xiaodan Yang; Ying Yin (Frontiers in Endocrinology, 2019)
Sclerostin knock-out mice or sclerostin antibody (Scl-Ab) treated wild-type mice displayed decreased marrow adiposity. But the effects of Scl-Ab on estrogen deficiency-induced marrow fat expansion remain elusive. In this work, 45 female New Zealand rabbits were equally divided into sham-operation, ovariectomy controls, and ovariectomy treated with Scl-Ab for 5 months. MR spectroscopy was performed to longitudinally assess marrow fat fraction at baseline conditions, 2.5 and 5 months post-operatively, respectively. We evaluated bone mineral density (BMD), bone structural parameters, serum bone biomarkers, and quantitative parameters of marrow adipocytes. Ovariectomized rabbits markedly exhibited expansion of marrow fat in a time-dependent manner, with a variation of marrow fat fraction (+17.8%) at 2.5 months relative to baseline and it was maintained until 5 months (+30.4%, all P < 0.001), which was accompanied by diminished BMD and deterioration of trabecular microstructure. Compared to sham controls, adipocyte mean diameter, adipocyte density and adipocytes area percentage was increased by 42.9, 68.3, and 108.6% in ovariectomized rabbits, respectively. Scl-Ab treatment increased serum bone formation marker and alleviated the ovariectomy escalation of serum bone resorption marker. It remarkably lessened the ovariectomy-mediated deterioration of BMD, and morphometric characteristics of trabecular bone. Marrow fat fraction was decreased significantly with Scl-Ab to levels matching that of sham-operated controls and correlated positively with reductions in adipocyte mean diameter, percentage adipocyte volume per marrow volume, and adipocyte density. Taken together, early Scl-Ab treatment reverts marrow fat expansion seen in ovariectomized rabbits in addition to having a beneficial effect on bone mass and microstructural properties.